LOKAKARYA PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA MELALUI PENDEKATAN KOMUNIKATIF BAGI GURU-GURU DI DESA CISONTROL, RANCAH, CIAMIS - Hendar, Hendar; Zuraida, Ida; Heryono, Heri; Astarina, Atri Nadia; Sujatna, Meita Lukitawati (Jurnal Abdimas Bina Bangsa, 2024)
Globalization has made the mastery of English a necessity not only in big cities, but also in the regions. Desa Cisontrol, Ciamis is one of the villages projected for the globalization of tourist villages. Thus, it is necessary to prepare Human Resources with good English language skills to support the program plan.  This Community Service activity aims to provide workshops related to improving students' English-speaking skills at the elementary, junior, and senior high school levels through a communicative approach for teachers at Desa Cisontrol. The communicative approach that focuses on students' communicative skills was raised as the main topic in accordance with the analysis of the needs for improving the communicative English skills of residents in preparation for the development plan of this village. The positive results of this Community Service activity are expected to provide long-term benefits as a solution to the problem of needs